Management of Small Unruptured Intracranial Aneurysms: A Survey of Neuroradiologists - Malhotra, A. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: The long-term history and management of unruptured intracranial aneurysms is not well understood. Our aim was to determine current practice patterns in the management of unruptured intracranial aneurysms, especially regarding imaging surveillance for conservatively managed aneurysms of this type. MATERIALS AND METHODS: An on-line survey was designed to examine physician practice and preference regarding the management of small unruptured intracranial aneurysms (≤7 mm in diameter). The survey was circulated to members of the American Society of Neuroradiology. Participation was voluntary, and all responses were anonymous. RESULTS: A total of 227 individual survey responses were obtained and included in the analysis with 54.6% (124/227) from diagnostic neuroradiologists (practicing >50% neuroradiology) and one-third (29%) from neurointerventional radiologists. One hundred seventy-three of 227 responded that routine, periodic imaging surveillance would be appropriate for conservatively managed unruptured intracranial aneurysms, and 84% of respondents recommended surveillance frequency of at least once a year. Fifty-nine percent favored indefinite, life-long follow-up for small unruptured intracranial aneurysms, and a similar number of respondents favored noncontrast MR angiography for aneurysm follow-up. Significant heterogeneity was found in size measurements used to assess aneurysms and criteria used to define growth on surveillance imaging. CONCLUSIONS: The natural history of intracranial aneurysms is not well-understood. A large proportion of incidentally detected, unruptured aneurysms are small (<7 mm). The survey results show significant heterogeneity in practice even among neuroradiologists and underlies the need to standardize imaging practice. Further studies are needed to assess the optimal frequency and duration of surveillance imaging for unruptured intracranial aneurysms. The criteria used to measure aneurysms and define growth on imaging also need to be standardized.